Eksistensi Pelinggih Tuan Aji Madura Sebagai Media Akulturasi Budaya Di Pura Dalem Dukun Sakti Desa Adat Tuban Kecamatan Kuta Kabupaten Badung - I Gusti Made Kusuma Dhana; Ni Nyoman Dian Tri Utami (Institut Agama Hindu Negeri Tampung Penyang Palangka Raya, 2023)
As a plural and multicultural country, conflict with religious background potentially occurs in Indonesia. Remembering that Pelinggih is a medium that functions as a place of worship so that it is sacred. However, in the aspect of communication, Pelinggih is understood as a medium to communicate messages visually, one of which is Pelinggih Tuan Aji Madura which is located at Dalem Dukun Sakti Temple, Tuban Customary Village. Dalem Dukun Sakti Temple is a temple belonging to the family of Arya Wang Bang Pinatih's descendants. Although this temple is a family temple, this temple also has loyal worshipers from all over Bali, but mainly Badung Regency and can be visited by all Dharma Hindu people throughout Indonesia on the basis of sraddha and is believed by local residents to be a temple that can cure all kinds of diseases. Cultural acculturation in this case through the Pelinggih Tuan Aji Madura media is unique, namely the shape made on it like the dome of a mosque. Many religions other than Hinduism pray at the Tuan Aji Temple, Madura. There are people who are Muslims who also come to pray at the Dalem Dukun Sakti Temple, especially at the Pelinggih Tuan Aji Madura. The Muslims who pray at Tuan Aji Madura have a belief that praying at Pura Dalem Dukun Sakti will heal them from their illness and are given medicine in the form of holy water that has been given by Tuan Aji Madura. The values ​​of Hindu Religious Education are contained due to such cultural acculturation, such as: Tattwa Education Values, Moral or Ethical Education Values, Ceremonial Education Values ​​and Tat Twam Asi Education Values.